Fluvial biofilm responses to joint changes in nutrients, temperature, turbidity and water velocity: an ex situ experiment - Cochero, Joaquín (2016)
The aim of this study was to explore the responses of the epipelic biofilm of a Pampean stream with little impact from human activity to two environmental conditions, with joint modifications in nutrients, temperature, water velocity and turbidity. The experiment was conducted using artificial channels and lasted five weeks. The biological variables measured included chlorophyll-a content, bacterial biomass, ash-free dry weight, total carbohydrate concentration, total respiratory activity, and biofilm composition. Results show that the species´ composition of the biofilm was affected, although no other structural or metabolic variables measured were. These results highlight the importance of including structural parameters to measure rapid changes in water quality, even when analyzing the effects of co-occurring variables.